Basic morphometric parameters of antlers in Roe deer (Capreolus capreolus L.) from imperial hunts in the Białowieża Primeval Forest - Urošević, Milivoje, veterinar (Array, 2021)
Roe deer (Capreolus capreolus L.) is adaptable to various habitat conditions and is widespread across Europe. The Białowieża Primeval Forest is an area in the moderate zone of lowland Europe and it is habitat for different game species. For the purposes of this study, the morphometric parameters of roe deer antlers shot in the Białowieża Primeval Forest by the Russian Czar Nicholas II during his reign (1894-1917) were analysed. Length of left and right beams, circumference of the left and right coronets, circumference of the left and right, length of the first and second tine end of the left and right beams, and inside span were measured and analysed. The results showed that during the imperial roe deer hunts in the period 1894 to 1917 in Białowieża Primeval Forest, individuals of similar morphometric trophy characteristics were hunted. The trophies were, on average, characterized by a slightly longer left beam, uniform beam circumference, coronet circumference, and very similar tine ends lengths.